2018
DOI: 10.1096/fj.201800642rr
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin mitigates subarachnoid hemorrhage injury primarily by increasing sirtuin 1 and inhibiting the Toll‐like receptor 4 signaling pathway

Abstract: Inflammation plays a key role in the progression of subarachnoid hemorrhage (SAH). Here, we examined the effects of astaxanthin (ATX) on the inflammatory response and secondary damage after SAH and the underlying mechanisms of action. In vivo, a prechiasmatic cistern injection model was established in rats and mice. In addition, neuron-microglia cocultures were exposed to oxyhemoglobin to mimic SAH in vitro. Western blotting revealed that protein expression of TLR4 was markedly increased in microglia at 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 74 publications
1
67
0
Order By: Relevance
“…TLR4 plays an important role in mediating the microglia-dependent neuroinflammation. The activation of TLR4 towards the M1 microglial polarization and increased expression of TLR4 are correlated with the poor outcomes in SAH [37][38][39] . TLR4 expression in microglia increases 2-6 h after SAH and remains elevated Figure 1.…”
Section: Microglial M1 Polarizationmentioning
confidence: 98%
See 1 more Smart Citation
“…TLR4 plays an important role in mediating the microglia-dependent neuroinflammation. The activation of TLR4 towards the M1 microglial polarization and increased expression of TLR4 are correlated with the poor outcomes in SAH [37][38][39] . TLR4 expression in microglia increases 2-6 h after SAH and remains elevated Figure 1.…”
Section: Microglial M1 Polarizationmentioning
confidence: 98%
“…TLR4 is markedly increased in microglia in a neuronmicroglia co-culture system in vitro, with consequent increases in pro-inflammatory cytokines and neuronal apoptosis. The downstream molecules, such as myeloid differentiation factor 88 (MyD88) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) are upregulated as well [37,38] . TLR4/MyD88/NF- Activation of TSG-6 and mGluR5 promotes microglial M2 polarization, therefore reverses the pro-inflammatory responses.…”
Section: Mediator Of Microglial Polarizationmentioning
confidence: 99%
“…Astaxanthin is also known to protect pancreatic beta cells by reducing oxidative stress and sugar toxicity, improve the levels of adiponectin and HDL, and enhances blood flow and circulations (14). nASX exerts broad-spectrum anti-inflammatory activities through multiple pathways (9,14,40,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). nASX significantly attenuate pathological elevation, critical inflammatory cell signaling nuclear factor kappa-B (NF-kB) pathway both in vitro and in vivo and reduce TNF-α in humans, resulting decrease in multiple pro-inflammatory cytokine level, which may potential in maintaining lung health and minimizing the impacts of SARS-CoV-2 infection (12)(13)(14).…”
Section: Astaxanthin Protects Against Inflammationmentioning
confidence: 99%
“…Fakhri et al (81) reported in a rat model that nASX prevented tissue and neuronal damages by downregulating NR2B, TNF-α and p-p38MAPK, and reported to improved sensory-motor function. In another study, Zhang et al (55) reported that nASX exert anti-inflammatory effect through increasing Sirtuin 1 (SIRT1) and inhibiting the Toll-like receptor 4 (TLR 4) signaling pathway resulting reduction of pro-inflammatory response and secondary brain injury. TLR4 express mainly in microglia and plays a pivotal role in triggering inflammatory response in the CNS (55).…”
Section: Astaxanthin As Neuroprotective Moleculementioning
confidence: 99%
See 1 more Smart Citation